2002
DOI: 10.4049/jimmunol.168.3.1028
|View full text |Cite
|
Sign up to set email alerts
|

Activation-Induced Expression of Carcinoembryonic Antigen-Cell Adhesion Molecule 1 Regulates Mouse T Lymphocyte Function

Abstract: Carcinoembryonic Ag cell adhesion molecule 1 (CEACAM1) consists of highly related homologs in humans and rodents that are characterized by significant alternate splicing generating isoforms capable of negative intracellular signaling by virtue of two immunoreceptor tyrosine-based inhibition motifs in its cytoplasmic (cyt) tail. Although human T cells have been recently observed to express CEACAM1, the expression and function of CEACAM1 in mouse T cells have not been defined. Although resting mouse spleen T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
101
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 45 publications
8
101
0
Order By: Relevance
“…Previous work noted that CEACAM1 is localized within intracellular granules in unstimulated murine T cells yet appears on the cell surface upon engagement of the TCR (38). We observed that CEACAM1 is also mobilized to the surface of activated human primary CD4 ϩ T cells upon exposure to either Abs that ligate the TCR or infection by N. gonorrhoeae.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Previous work noted that CEACAM1 is localized within intracellular granules in unstimulated murine T cells yet appears on the cell surface upon engagement of the TCR (38). We observed that CEACAM1 is also mobilized to the surface of activated human primary CD4 ϩ T cells upon exposure to either Abs that ligate the TCR or infection by N. gonorrhoeae.…”
Section: Discussionsupporting
confidence: 60%
“…The intracellular storage of these coinhibitory receptors presumably facilitates an early sensitivity to TCR-dependent activating signals, with subsequent diminution as CEACAM1 is delivered to the cell surface. (60) are not phosphorylated (38). This exposes binding motifs for the clathrin adaptor protein AP-1 (38) and AP-2 (24), which promote receptor internalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 In contrast, in mouse spleen T lymphocytes, CEACAM1 was not present on the surface of resting cells but was rapidly up-regulated on CD4 ϩ and CD8 ϩ T cells after activation with either Con A or anti-CD3 stimulation. 36 Overall, these studies in leukocytes are somewhat different from the CEACAM1 expression profile that we have observed in murine and human platelets with moderate basal expression on the surface of resting platelets with an intracellular pool evident (Figure 1A-D). This difference Figure 5.…”
Section: Discussionmentioning
confidence: 42%